2008
DOI: 10.1371/journal.pbio.0060060
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Mismatches Reveal Escape from Arms-Race Coevolution

Abstract: Because coevolution takes place across a broad scale of time and space, it is virtually impossible to understand its dynamics and trajectories by studying a single pair of interacting populations at one time. Comparing populations across a range of an interaction, especially for long-lived species, can provide insight into these features of coevolution by sampling across a diverse set of conditions and histories. We used measures of prey traits (tetrodotoxin toxicity in newts) and predator traits (tetrodotoxin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
247
1
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(262 citation statements)
references
References 82 publications
(148 reference statements)
7
247
1
7
Order By: Relevance
“…The coevolutionary process continues until stopped by tradeoffs imposed on populations by other requirements, such as the need to compete with other species, find mates, or rear offspring. How natural selection balances all these conflicting demands varies among environments, leading sometimes to complex geographic patterns in levels of defense and counter-defense in interacting species (Hanifin et al 2008). Over longer geological time scales, these coevolutionary arms races have fueled some of the diversification of life (Ehrlich and Raven 1964;Farrell 1998;Becerra et al 2009;McKenna et al 2009;Segraves 2010).…”
Section: Coevolution Takes Multiple Forms and Generates A Diversity Omentioning
confidence: 99%
See 1 more Smart Citation
“…The coevolutionary process continues until stopped by tradeoffs imposed on populations by other requirements, such as the need to compete with other species, find mates, or rear offspring. How natural selection balances all these conflicting demands varies among environments, leading sometimes to complex geographic patterns in levels of defense and counter-defense in interacting species (Hanifin et al 2008). Over longer geological time scales, these coevolutionary arms races have fueled some of the diversification of life (Ehrlich and Raven 1964;Farrell 1998;Becerra et al 2009;McKenna et al 2009;Segraves 2010).…”
Section: Coevolution Takes Multiple Forms and Generates A Diversity Omentioning
confidence: 99%
“…The traits of the conifers and the crossbills show just the kinds of geographic differences you would expect to find in regions with squirrels as compared with regions without squirrels (Edelaar and Benkman 2006;Siepelski and Benkman 2007;Parchman and Benkman 2008;Benkman and Parchman 2009;Benkman 2010). Toxic newts and the garter snakes that eat them differ geographically in western North America in the level of chemical defenses in the newts and the ability of the snakes to detoxify those chemical defenses (Brodie et al 2002;Brodie et al 2005;Hanifin et al 2008). Wild parsnips and parsnip webworms, introduced to North America from Europe only within the past few hundred years, have coevolved into a geographic mosaic in the mix of chemical defenses deployed by the plants against these insects and the detoxification enzymes in the insects that counteract these defense chemicals (Berenbaum and Zangerl 1998;Zangerl and Berenbaum 2003).…”
Section: Interactions Coevolve As Constantly Changing Geographic Mosaicsmentioning
confidence: 99%
“…Divergence in morphology has been a dominating theme of coevolutionary studies (for recent examples see e.g. Benkman et al 2012;Pauw et al 2009; Toju et al 2011), but studies of chemical diversification increasingly have shown that coevolution is just as often about attractants, repellents, toxic compounds, and counter responses to those compounds (Berenbaum and Zangerl 2006;Brodie and Ridenhour 2003;Ehrlich and Raven 1964;Foitzik et al 2003;Hanifin et al 2008;Johnson et al 2010;Raguso 2008;. Attractants are a particularly intriguing class of compounds in coevolving interactions, because they actively attract mutualists but may simultaneously attract enemies (Theis and Adler 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Because adaptive traits of interacting species often vary among populations, these studies aimed to substantiate whether complementary traits were closely correlated across the distributional range of the interaction as evidence of coevolution [7,9,11,12]. Trait covariation, however, should not unequivocally be interpreted as being due to reciprocal selection as it may emerge in unilaterally evolved systems as well [13].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the existence of trait covariation across the distributional range of the interaction does not imply perfect trait matching between interacting organisms at the population level. Examples of trait mismatch, where the most extreme trait in one species does not produce an ecological effect in the most extreme trait of the interacting species, include studies of trait correlation between pollinators and plant floral morphologies (reviewed by Anderson et al [10]), between parasites and the size of the plant defensive apparatus [8], or between prey and predator traits [9]. Trait mismatch has commonly been considered the consequence of the existence of coevolutionary coldspots, where the interacting species may not experience reciprocal selection or due to gene flow into hotspots that hampers local adaptation [1,2].…”
Section: Introductionmentioning
confidence: 99%